Internet Of Things (IoT) Integration In Telecommunication Networks: Challenges and Opportunities - Agi Nanjar; Titi Safitri Maharani; Priyo Agung Prastyo; Muhammad Taufik Nur Hidayat; Imam kharits najibulloh (University of Science and Computer Technology, 2024)
This research delves into the challenges and opportunities posed by integrating Internet of Things (IoT) into telecommunication networks. It focuses on understanding IoT fundamentals, identifying hurdles like security and data management, and exploring prospects such as new services and operational streamlining. By analyzing government roles and strategic planning, it aims to harness the full potential of IoT-telecom convergence. Adopting a qualitative approach, this study aims to offer profound insights into the complexities of this integration. Through examining challenges and opportunities, it strives to contribute significantly to technological and societal advancement. Emphasizing literature review techniques and focused data analysis, this research aims to inform policy, foster innovation, and deepen comprehension of advanced technology's impact. IoT links physical devices to the internet, enabling innovations like smart homes and environmental monitoring, while telecom networks facilitate data exchange with a focus on infrastructure development and security. Integration of IoT into these networks enhances efficiency and security, with forecasts indicating continued expansion of IoT's role in telecom networks.